Physical, mechanical, and biodegradable properties of meranti wood polymer composites - Hoque, M. Enamul; Aminudin, M. A. M.; Jawaid, Mohammad; Islam, Md. Saiful; Md. Tahir, Paridah (Elsevier, 2014)
In-situ polymerization and solution casting techniques are two effective methods to manufacture wood polymer composites (WPCs). In this study, wood polymer composites (WPCs) were manufactured from meranti sapwood by solution casting and in-situ polymerization process using methyl methacrylate (MMA) and epoxy matrix respectively. Physical, mechanical, and morphological characterizations of fabricated WPCs were then carried out to analyse their properties. Morphological properties of composites samples were analyzed through scanning electron microscopy (SEM). The result reveals that in-situ wood composite exhibited better properties compared to pure wood, 5% WPC and 20% WPC. Moreover, in-situ WPC had lowest water absorption and least biodegraded. Conversely, pure wood shown moderate mechanical strength, high biodegradation and water absorption rate. In term of biodegradation, earth-medium brought more severe effect than water in deteriorating the properties of the specimens.